Neolithic Stepping Stones : Excavation and Survey Within the Western Seaways of Britain, 2008-2014 - Garrow, Duncan (Oxbow Books, Limited, 2017)
Cover -- Book Title -- Copyright -- Contents -- List of figures -- List of tables -- Acknowledgements -- Chapter 1. Introduction -- 1.1. Introduction to the Stepping Stones project -- 1.2. The Mesolithic-Neolithic transition in Britain, Ireland and north-west France -- 1.3. The 'western seaways' -- 1.4. The changing palaeogeography of Britain and Ireland -- Channel Islands -- Isles of Scilly -- Outer Hebrides -- Summary -- 1.5. Early Neolithic settlement in Britain and Ireland -- 1.6. The Mesolithic, Neolithic and Early Bronze Age archaeology of the Channel Islands, Isles of Scilly and Outer Hebrides -- Channel Islands -- Isles of Scilly -- Outer Hebrides -- 1.7. Volume overview: key themes -- Chapter 2. L'Erée, Guernsey, Channel Islands -- 2.1. Introduction -- Geology and topography -- Previous work at the site -- Research objectives -- 2.2. Survey and excavation strategy -- Survey strategy -- Excavation strategy -- Excavation methodology -- 2.3. Results -- The soil sequence -- Artefact distributions within the stratifi ed deposits -- Archaeological features -- 2.4. Prehistoric pottery (by Anwen Cooper) -- 2.5. Chipped stone (by Anne Pirie & Donovan Hawley) -- 2.6. Worked stone (by Duncan Garrow & John Renouf) -- 2.7. Micromorphology (by Charles French) -- 2.8. Environmental analysis (by Julie Jones, Rob Scaife and Fraser Sturt) -- 2.9. Radiocarbon dating (by Duncan Garrow & Seren Griffiths) -- 2.10. Discussion: Mesolithic to Bronze Age occupation at L'Erée -- Chapter 3. Old Quay, St Martin's, Isles of Scilly -- 3.1. Introduction -- Geology, topography and environment -- Previous work at the site -- Research objectives -- 3.2. Excavation strategy and methodology -- 3.3. Results -- The soil sequence -- Artefact distributions -- Archaeological features -- 3.4. Prehistoric pottery (by Henrietta Quinnell with Roger Taylor).